Helsinki Memorandum of Understanding as a sluggish policy: A critical discourse analysis with process types - Rahman, Mustafa A. (Studies in English Language and Education, 2023)
Helsinki Memorandum of Understanding (MoU) between the government of Indonesia (GoI) and the Free Aceh Movement (GAM) celebrated its 18th anniversary in 2023. However, its discursive aspect and efficacy are still under-researched. This article aims to analyze the process types in the Helsinki MoU text and explore the policy implementation of the agreement on the social changes in Aceh. The MoU document was retrieved from the United Nations peacemakers website. Mixed methods with descriptive statistics were used to identify, interpret, and explain the data. Hallidayan systemic linguistics was employed to identify the process types and the transitivity patterns. Critical discourse analysis (CDA) as an explanatory critique was applied to critical social analysis. The findings show that the material processes dominated the Helsinki MoU text (73%), followed by the relational processes (18%), and verbal processes (4%). The actors were generally in the form of concepts and sometimes obfuscated. Meanwhile, the goals were also mostly realized by concepts. Explanatory critique reveals that there was a vagueness and hidden power relation between the GoI and GAM in the peace deal. The GoI has also been inconsistent with some of the agendas. The Helsinki MoU has yet to produce comprehensive outcomes for Acehs development and has seemingly served as a bureaucratic means of control. The current study has limited itself to the single MoU text. Therefore, for deeper inquiries further research should focus on multiple similar texts and use a different research design, including intertextuality, questionnaires, and interviews.